Physical fitness in youth basketball players in pre and post season under a strength program effect - Forte, Pedro (2016)
Basketball it’s an acyclic modality characterized by an intermittent effort, direction changes and a hypersolicitation of upper and lower limbs. Thus, it depends of a physical excellence to individual or collective performance improvement. The aim of this study was to evaluate the physical fitness in youth basketball players in pre-season and post-season under a strength program.